2012
DOI: 10.1002/term.1648
|View full text |Cite
|
Sign up to set email alerts
|

Novel naturally crosslinked electrospun nanofibrous chitosan mats for guided bone regeneration membranes: material characterization and cytocompatibility

Abstract: Guided bone regeneration (GBR) barrier membranes are used to prevent soft tissue infiltration into the graft space during dental procedures that involve bone grafting. Chitosan materials have shown promise as GBR barrier membranes, due to their biocompatibility and predictable biodegradability, but degradation rates may still be too high for clinical applications. In this study, chitosan GBR membranes were electrospun using chitosan (70% deacetylated, 312 kDa, 5.5 w/v%), with or without the addition of 5 or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 17 publications
5
52
0
Order By: Relevance
“…In any case, consistent with above SEM results, we found cell viability was sharply enhanced when cultivated on the 0.5%GP crosslinked CTS nanofibers as compared to other GP concentrations, which indicates that CTS-GP0.5% nanofibers could be used as the optimal scaffold for cell growth. Earlier on, Bumgardner's group demonstrated in vitro the cytocompatibility of electrospun nanofibrous CTS membranes crosslinked with GP by culturing with fibroblast, ostoblast, and monocyte cell lines (Norowski et al, 2012(Norowski et al, , 2015. Very recently, it was found that these crosslinked nanofibrous CTS membranes also exhibited similar inflammatory and tissue Fig.…”
Section: Viability Of Fibroblast Cells On Gp-crosslinked Nanofibrous mentioning
confidence: 92%
“…In any case, consistent with above SEM results, we found cell viability was sharply enhanced when cultivated on the 0.5%GP crosslinked CTS nanofibers as compared to other GP concentrations, which indicates that CTS-GP0.5% nanofibers could be used as the optimal scaffold for cell growth. Earlier on, Bumgardner's group demonstrated in vitro the cytocompatibility of electrospun nanofibrous CTS membranes crosslinked with GP by culturing with fibroblast, ostoblast, and monocyte cell lines (Norowski et al, 2012(Norowski et al, , 2015. Very recently, it was found that these crosslinked nanofibrous CTS membranes also exhibited similar inflammatory and tissue Fig.…”
Section: Viability Of Fibroblast Cells On Gp-crosslinked Nanofibrous mentioning
confidence: 92%
“…Genipin at 5 or 10 m M concentration was added to the chitosan solution 30 min before electrospinning. The concentrations of genipin were selected based on our previous studies that showed statistical differences in tensile strengths and in vitro degradation of the membranes . Electrospinning was performed using a plastic 10 mL syringe with a blunt 20 G, 3.81 cm stainless steel needle tip, at a 20 μL/min flow rate, and a voltage of 25 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes were allowed to dry, were then cut in 1 × 1 cm specimens. Genipin crosslinked and uncrosslinked chitosan electrospun membranes under these conditions have average fiber diameters of 142 and 162 nm, respectively, and average tensile strengths 32.2 MPa (10 m M genipin crosslinked), 22.2 MPa (5 m M genipin crosslinked), and 12.3 MPa (uncrosslinked chitosan) and the membranes produced are approximately 0.05 mm thick . Membranes were sterilized by ethylene oxide gas (24 h exposure, 2 h ventilation, ∼20°C and >35% relative humidity) before implantation (Anprolene Gas Sterilizer, Model AN74i, Andersen Products, NC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed electrospun chitosan membranes with genipin cross-linking (natural crosslinker) that have resulted in 12% reduction in mass loss over 16 weeks, and increased the tensile strength of the membranes three fold [9]. We have also demonstrated that the genipin crosslinked chitosan membranes were not cytotoxic to osteoblast or fibroblast cells, and did not cause monocyte activation.…”
Section: Introductionmentioning
confidence: 99%